2010
DOI: 10.1002/ijc.25569
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke induces promoter methylation of single‐stranded DNA‐binding protein 2 in human esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is the sixth most frequent cause of cancer death in the world, and cigarette smoke is a key factor in esophageal carcinogenesis. To identify molecular changes during cigarette smoke-induced ESCC, we examined the methylation status of 13 gene promoters in the human immortalized, nontumorigenic esophageal epithelial cell line (Het-1A) that were exposed to mainstream (MSE) or sidestream cigarette smoke extract (SSE) for 6 months in culture. The promoter of sequence-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…Wet laboratory work, which could experimentally address the presence and consequences of methylation changes in cardiovascular candidate genes that could be caused by tobacco smoke exposure in appropriate cell cultures, seems to be altogether lacking. Successful proof-of-concept for such investigations can be found in the literature on malignant sequelae of smoking, 41 including follow-up studies to support the functional relevance of hits from an epigenome-wide methylation screen. 42 …”
Section: Arterioscler Thromb Vasc Biol July 2013mentioning
confidence: 99%
“…Wet laboratory work, which could experimentally address the presence and consequences of methylation changes in cardiovascular candidate genes that could be caused by tobacco smoke exposure in appropriate cell cultures, seems to be altogether lacking. Successful proof-of-concept for such investigations can be found in the literature on malignant sequelae of smoking, 41 including follow-up studies to support the functional relevance of hits from an epigenome-wide methylation screen. 42 …”
Section: Arterioscler Thromb Vasc Biol July 2013mentioning
confidence: 99%
“…Tobacco contains more than 60 carcinogens (Hoffmann et al, 1990;Hecht et al, 2006) and tobacco exposure is known to induce genetic and epigenetic changes in esophageal squamous and lung cancer cells (Hecht et al, 1999;Soma et al, 2006;Liu et al, 2007;Lin et al, 2010;Huang et al, 2011). NNK is a key ingredient of tobacco smoke carcinogens.…”
Section: -(Methylnitrosamino)-1-(3-pyridyl)-1-butanone Induces Retinmentioning
confidence: 99%
“…As further evidence of the biologic plausibility of these findings, SSBP2 has been reported to be involved in the maintenance of genome stability (29) and has been implicated in transcriptional signatures in several cancers including leukemia, (30) pancreatic cancer, (31) oligodendroglial tumors, (32) and esophageal squamous cell carcinoma. (29) A direct confirmation of the link between SSBP2 and survival in brain cancer is further proffered by Shaw et al, (32) in which the expression of SSBP2 was shown to be associated with response to chemotherapy in patients with oligodendroglial tumors.…”
Section: Discussionmentioning
confidence: 98%